Math principles for food service occupations - Strianese, Anthony J.; Strianese, Pamela P. (Delmar, Cengage Learning, 2012)
Uses a step-by-step method to teach basic math principles that affect everything from recipe preparation to managing food and labor costs in a restaurant operation.